Determination of Risk Factors of Osteoporosis in the Community of Post-Menopausal Age: Risk Factors of Osteoporosis - Perveen, Rukhsana; Shabbir, Anbreen; Azad, Zainab; Azad, Amna (Pakistan Journal of Health Sciences, 2023)
Osteoporosis is a major and significant health problem in old aged people and especially in female. Osteoporosis is characterized by low bone mineral density (BMD). The associated factors of osteoporosis are not well-understood in local population specifically in females. Objective: To determine the risk factors of osteoporosis in community of post-menopausal age. Methods: This cross-sectional study was conducted at H-Block Nishat Colony, Lahore Cantonment Area, Lahore during March 2020 to June 2020, the study population was post-menopausal women of age between 45 years to 65 years and women who fulfilled the inclusion criteria were recruited as sample using convenience sampling. A self-designed questionnaire was used to get demographic and diseased related factors. Chi-square (χ2) was used to measure association between disease and risk factors. Results: Among 200 women of post-menopausal age 61.2% were found with osteoporosis, mostly were aged between 51-54 years. There was a significant association with increasing age (p<0.001) Other significant factors were marital status, family history of osteoporosis, physical activity, soda intake and medication. Conclusions: In conclusion, this our discussion sheds light on the risk factors associated with osteoporosis within the postmenopausal community. The identified risk factors, including diminished BMD, emphasize the importance of proactive measures and targeted interventions to mitigate the consequences of osteoporosis in postmenopausal age group. Addressing these risk factors not only holds the potential to enhance the overall well-being of individuals but also contributes to a broader community-wide approach to promoting bone health. <span class="EOP SCXW140653995 BCX0" data-ccp-props=""201341983":0,"335551550":6,"335551620":6,"335559739":0,"335559740":240,"469777462":[3600,3960,4320,4680,5040,5400,5760,6120,6480,6840,7200,7560,7920,8280,8640,9000,9360,9720,10080,10440,10800,11160,11520],"469777927":[0,0,0,0,0,0,0,0,0,0,0,0,0,0,0,0,0,0,0,0,0,0,0],"469777928":[1,1,1,1,1,1,1,1,1,1,1,1,1,1,1,1,1,1,1,1,1,1,1]">